International insurance?: Democratic consolidation and support for international human rights regimes - Zschirnt, Simon (International journal of transitional justice, 2014)
Judicial empowerment has traditionally been explained as a response to political uncertainty. This article applies this insight to the international context to explain patterns of support for the empowerment of supranational courts. Our analysis of the negotiations that produced the International Criminal Court suggests that the relationship between democratic consolidation and support for empowering such courts is curvilinear. States with no recent experience with the type of autocratic regime particularly likely to commit serious human rights violations generally favored a somewhat weaker Court. In this respect their positions sometimes aligned with those of autocracies. Conversely, states that had recently emerged from the shadow of autocratic rule, for whom the sovereignty costs associated with the Court were countervailed by the benefit of insurance against backsliding toward autocracy, generally favored a stronger Court. Thus, just as uncertainty drives judicial empowerment in domestic contexts, it also drives judicial empowerment in the international context.